Korelasi Antara Panjang Tulang Radius Dengan Tinggi Badan Pada Suku Batak di Universitas HKBP Nommensen Medan - Genta Suci Anggitya Tobing; Saharnauli Janna Verawaty Simorangkir; Jenny Ria Sihombing (Universitas HKBP Nommensen, 2021)
Background: Dead victim and/ or found in unregocnized condition need to be identified. The identification of the unrecognized victim is carried out to prove that the skeleton is a human skeleton with ethnicity, race, sex, estimated age, height and special characteristics. Body height is a main characteristic which used as an identification process for various interests. Estimated body height can be measured based on long bones, which one of them is radius bone. Objective: This study aimed to determine the correlation between the length of the radius bone with body height of Bataknese student, lecturer, and staff at Universitas HKBP Nommensen Medan. Method: This research was an analytic study with cross-sectional design. The sample of this study was 72 students and employees of Universitas HKBP Nommensen Medan, consist of 27 Bataknese men and 45 Bataknese women who met the inclusion and exclusion criteria. Sampling technique was done by purposive sampling. Data analysis was done by univariate method to describe the characteristics of the subjects, normality test used the Kolmogorov-Smirnov test and bivariate analysis used the Pearson and Spearman tests to obtain the correlation between the radius bone length and body height. Results: The results of the study by sex, both men and women have a strong correlation value. Men have a correlation strength with r = 0.746 (p>0.05) and women have a correlation strength with r = 0.789 (p<0.05). Conclusion: There is a strong correlation between the length of the radius bone with body height of Bataknese students at Universitas HKBP Nommensen Medan.